2022
DOI: 10.1101/2022.03.02.482598
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inducible CRISPR/Cas9 allows for multiplexed and rapidly segregated single target genome editing in Synechocystis sp. PCC 6803

Abstract: Establishing various synthetic biology tools is crucial for the development of cyanobacteria for biotechnology use, especially tools that allow for precise and markerless genome editing in a time-efficient manner. Here we describe a riboswitch-inducible CRISPR/Cas9 system, contained on one single replicative vector, for the model cyanobacteria Synechocystis sp. PCC 6803. A theophylline-responsive riboswitch allowed tight control of Cas9 expression, which enabled reliable transformation of the CRISPR/Cas9 vecto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…To our knowledge, only one recent study reported multiplex genome editing in cyanobacterium Synechocystis sp. PCC 6803 (37), and no such progress in S. elongatus have been documented. We explored the potential of base editing in multiplexing with tandem gRNA cassettes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one recent study reported multiplex genome editing in cyanobacterium Synechocystis sp. PCC 6803 (37), and no such progress in S. elongatus have been documented. We explored the potential of base editing in multiplexing with tandem gRNA cassettes.…”
Section: Resultsmentioning
confidence: 99%
“…To build a base-editing system, we also need to overcome these obstacles. First, we employed dCas9 as the CRISPR effector, which exhibits low toxicity and has been promoting inspiring progress in cyanobacteria (37, 47). The lacI -P trc inducible system was utilized to drive the editing module for reducing the toxicity furthermore.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to UTEX 2973 with 2 mM theophylline added [20], we observed a 3-fold increase in the intensity of theophylline-induced riboswitch expression in our optimized constructions (as measured by Miller values). This strategy can be further explored in future studies by switching to -10-box sequences with moderate promoter strength or employing other riboswitches with reduced leakage expression [49].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the over-expression intensity of Ptrc, which has the same -10-box sequence as PJ23119 (TATAAT), might cause the failure of the riboswitch. Therefore, we adapted two alternative strategies: i) replacing the -10-box of Ptrc with the -10-box from the weakly expressed promoters; ii) replacing theoE*with a much less leaky B-type riboswitch (theoB) [49]. We evaluated the -10-boxes from PJ23118 (-10-box: TATTGT), PJ23105 (-10-box: TACTAT) and PJ23114 (-10-box: TACAAT) as alternatives by using the last three digits (118,105,114) to represent them.…”
Section: Characterization Of Constitutive Promoters and Inducible Pro...mentioning
confidence: 99%
“…Another way is to control the expression of the CRISPR-Cas system tightly. Hudson and colleagues hired a tightly regulated RNA device, the theophylline-responsive riboswitch, to maintain a low enough OFF-state expression of Cas9 to prevent its toxicity, and induce the genome-editing when required ( Cengic et al, 2022 ). By applying this system, the reliable transformation of a replicable plasmid harboring CRISPR-Cas9 was obtained, leading to successful deletions and insertions of DNA fragments in the genome of Synechocystis .…”
Section: Crispr-cas-based Genome Editingmentioning
confidence: 99%